Headache Education by E-Learning Through Social Networking Services (Social Media) - Katsuki M; Nanri M; Miyakoshi Y; Gobo S; Koh A; Kawamura S; Tachikawa S; Matsukawa R; Kashiwagi K; Matsuo M; Yamagishi F (Dove Medical Press, 2023)
Masahito Katsuki,1,2 Maiko Nanri,3 Yuki Miyakoshi,4 Shuto Gobo,4 Akihito Koh,2 Shin Kawamura,2 Senju Tachikawa,2 Ryo Matsukawa,2 Kenta Kashiwagi,5 Mitsuhiro Matsuo,6 Fuminori Yamagishi7 1Department of Neurosurgery and Headache Outpatient, Japanese Red Cross Suwa Hospital, Nagano, Japan; 2Department of Neurosurgery, Itoigawa General Hospital, Niigata, Japan; 3Nurse-Senka, SMS Corporation, Tokyo, Japan; 4Creatone, Regnition, Saitama, Japan; 5Department of Neurology, Itoigawa General Hospital, Niigata, Japan; 6Department of Anesthesiology, Toyama University Hospital, Toyama, Japan; 7Department of Surgery, Itoigawa General Hospital, Niigata, JapanCorrespondence: Masahito Katsuki, Department of Neurosurgery, Japanese Red Cross Suwa Hospital, 5-11-50, Kogandori, Suwa, Nagano, 392-0027, Japan, Tel/Fax +81-0266-52-6111, Email ktk1122nigt@gmail.comIntroduction: Headache is a common public health problem, but its burden could be avoided by raising headache awareness and the appropriate use of acute medication and prophylactic medication. Few reports on raising headache awareness in the general public have been reported, and there are no reports on headache awareness campaigns through social networking services (SNS), or social media, in Japan. We prospectively performed a headache awareness campaign from March 2022 through 2 SNS, targeting nurse and wind instrumental musicians, because they are with high headache prevalence.Methods: Through the 2 SNS, the article and video were distributed, respectively. The article and video described the 6 important topics for the general public about headaches, which were described in the Clinical Practice Guideline for Headache Disorders 2021. Just after reading or watching them as e-learning, we performed online questionnaire sheets to investigate the awareness of the 6 topics through the 2 SNS. The awareness of the 6 topics before and after the campaign was evaluated.Results: In the SNS nurse-senka, we obtained 1191 responses. Women comprised 94.4%, and the median (range) age was 45 (20 to 71) years old. Headache sufferers were 63.8%, but only 35.1% had consulted doctors. In the SNS Creatone, we got the response from 134 professional musicians, with 77.3% of women. The largest number of respondents were in their 20s (range 18- 60 years old). Headache sufferers were 87.9%. Of them, 36.4% had consulted doctors, 24.2% were medication-overuse headache. The ratios of individuals who were aware of the 6 topics significantly increased from 15.2%-47.0% to 80.4- 98.7% after the online questionnaire in both SNS (p < 0.001, all).Conclusion: E-learning and online survey via SNS can improve headache awareness.Keywords: awareness, education, medication-overuse headache, migraine, online, prevention, social networking services, social media